Students’ Ability In Using Conditional Sentences At State Islamic Senior Highschool 2 Pekanbaru - Ayu Sekar Sari; Yani Lubis; Annisa Eka Putra Aulia (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Conditional sentences are one of the materials taught in English subject at the eleventh grade of Senior High School, in which the students are expected to apply social function, text structure, and language components of English written and spoken, in terms of expressing plan according to the context used. Based on the preliminary research, it was found that the teacher has tried her best in teaching by using some strategies to achieve the learning goals, yet the students still got some difficulties, such as inability to put correct verb in each type, to use correct tense, to arrange clauses in each type, to identify the form in each type. This research was aimed to describe the students’ ability in using conditional sentences and to investigate the dominant type of conditional sentences mastered by the eleventh-grade students in using conditional sentences (type I, II, and III) at State Islamic Senior High School 2 Pekanbaru. The design of this research was descriptive quantitative research and the instrument used in this research was an objective test or multiple choice. The population of this research was 210 students. Then, the researcher used a simple random sampling technique to take the sample and chosen 30 students. By using SPSS 22.0 in analyzing the data, the researcher found out: first, the mean score of students’ ability in using conditional sentences was 77.86, it was categorized as a “good” level; second, the dominant type of students’ ability in using conditional sentences was “type I” with a mean score of 0.88 or 38%. It means the process of teaching and learning English, more specifically, in Conditional Sentences, at State Islamic Senior High School 2 Pekanbaru has been optimum, but keep varying the teaching models in order to achieve the effective learning.